Fostering fisheries futures: the promise of localized stewardship education in Nunatsiavut - Laver, Quinna; Andersen, Ola; Moore, Sylvia; Pottle, Colleen; Snook, Jamie (Frontiers in Environmental Science, 2024)
Nunatsiavut is a self-governing Inuit territory in northern coastal Labrador, where cultural knowledge and social values are incorporated into co-managed subsistence and commercial fisheries. Snow crab (Chionoecetes opilio), known as Putjotik in Inuttitut (the Nunatsiavut dialect of Inuktitut), is a co-managed fishery through the Torngat Joint Fisheries Board (TJFB) and plays a crucial role in sustaining the community of Makkovik. Arctic Char (IKaluk) is also harvested in co-managed subsistence and commercial fisheries, and is a staple in local economies and culture. In 2022, the TJFB partnered with Inuit educators to foster youth stewardship in a project called Paigitsiaguk. The Paigitsiaguk project bridges Inuit and scientific knowledge to nurture cultural values and environmental stewardship through providing place and land-based resources to educators. The project team created a comprehensive database of curriculum outcomes required by the Newfoundland and Labrador school system, and then designed culturally relevant learning activities that presented Inuit knowledge with science and social studies for students in Nunatsiavut. These resources include learning activities that are organized into education kits: one of which is centered on Putjotik and another on IKaluk. The Putjotik kit has 23 activities tailored to meet grade-specific learning outcomes, while the IKaluk kit provides 12 place-based learning activities appropriate for multiple grade levels. By providing localized and culturally relevant education resources to teachers that revolve around stewarding local fish species and their ecosystems, youth are connecting to their communities and to the coastal environment. Educational resources and learning activities reflect Inuit and scientific knowledge systems, and position teachers as facilitators to encourage students to learn from the land and Elders, knowledge holders, fishers, scientists, and managers. This paper reflects the promising futures that this work can contribute to; from facilitating intergenerational knowledge transmission from knowledge holders to youth, to encouraging self-determined stewardship activities that encourage care for the ocean and its fisheries.